Simulation of Static Loading on the Automatic Folding Clothes Hanger by Using Autodesk Fusion 360 - Sukendro Broto Sasongko; Agung Subekti (Department of Mechanical Engineering, Universitas Andalas, 2024)
Simulation of the static loading to the folding frame of the clothes hanger investigated by using Software Autodesk Fusion 360. The strength of the folding frame is important during hanging the clothes weight. The simulation of loading of wet clothes was by Autodesk Fusion 360 and performed in real life. The loads spread to three positions, which those locations investigated as critical locations. The locations are at short distance X1, medium X2, and far X3; the zeroing is from the wall. The simulation performs Von Misses procedure for the loading analysis. Thus, the result of the analysis responds to the external load at the joints of the structure. The loads are the weight of the wet clothes during drying time. The bar aluminum structure connects its parts using hinges. Simulation result obtains data of loading. Further, displacement analysis completes those data. The safety factor was at the frame loading simulation. That is, those data are in by Von Misses stress-strain analysis. The result reveals the effect of the frame loading. The process of loading 12 kg induces a safety factor 3.746, normal stress 73.42 Mpa, and a displacement of structure bar 6.452 mm. At loading 22 kg obtains the safety factor 2.038, maximum stress 134.9 Mpa, and the displacement 9.86 mm. Furthermore, loading 37 kg-load, the safety factor 1.21, prime stress enlarges 61.48 Mpa, and the displacement was larger by 10.97 mm. Therefore, the simulation result concludes the weight of clothes trends a linear effect on the loading of part joints. The frame structure is tough to the weight of dry clothes and safe, deformation of the bar is less than 10 % of normalizing for 37 kg-loading.